2010
DOI: 10.1111/j.1469-185x.2010.00160.x
|View full text |Cite
|
Sign up to set email alerts
|

Fitting statistical models in bivariate allometry

Abstract: Several attempts have been made in recent years to formulate a general explanation for what appear to be recurring patterns of allometric variation in morphology, physiology, and ecology of both plants and animals (e.g. the Metabolic Theory of Ecology, the Allometric Cascade, the Metabolic-Level Boundaries hypothesis). However, published estimates for parameters in allometric equations often are inaccurate, owing to undetected bias introduced by the traditional method for fitting lines to empirical data. The t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
73
1
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(77 citation statements)
references
References 87 publications
0
73
1
3
Order By: Relevance
“…2 had statistically significantly nonzero linear coefficient b (with P < α; here α = 0.05), and if a least-squares quadratic regression between the independent variable log(mean) and dependent variable log(variance) did not yield a statistically significant quadratic coefficient c (P > α). The use of the doubly logarithmic scale in the testing of TL and other bivariate allometric relationships (e.g., scaling of metabolic rate with body mass) has been questioned (39,(42)(43)(44) and defended (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…2 had statistically significantly nonzero linear coefficient b (with P < α; here α = 0.05), and if a least-squares quadratic regression between the independent variable log(mean) and dependent variable log(variance) did not yield a statistically significant quadratic coefficient c (P > α). The use of the doubly logarithmic scale in the testing of TL and other bivariate allometric relationships (e.g., scaling of metabolic rate with body mass) has been questioned (39,(42)(43)(44) and defended (45,46).…”
Section: Methodsmentioning
confidence: 99%
“…The lack of homoscedasticity of the data in the linear model represents an important drawback, as pointed out also in the original discussion of the DEPM (Daily Egg Production Method) method Lasker 1985). In addition, Packard et al (2011), who discuss the abuse of the allometric model, support the power curve model as an appropriate means to achieve data homoscedasticity. In the present case, the selection of the power curve model was furthermore feasible because of the virtual sameness of the MSE values derived from both the linear and the power curve models.…”
Section: Discussionmentioning
confidence: 99%
“…The imprecision of the model observed in this study might have been introduced by the rotational distortion that accompanies regression analyses performed on logarithms. Because of the nonlinear relationship between values expressed in arithmetic and logarithmic scales, small arithmetic values for predictor and response have a much greater influence than large values on parameters (scaling coefficient, β 0 , and exponent, β 1 ) of the linear equations fitted on logarithmic transformations [36].…”
Section: Discussionmentioning
confidence: 99%
“…The most recent allometric research in trees and forests tends to focus on explaining the scaling of structural and functional properties of trees with measures of their body sizes (e.g., diameters, heights) [36]. West et al [29] suggested that the scaling exponent (β 1 ) should scale against tree diameter with a universal exponent β 1 ≈ 2.67 on trees whose height increments are at their maximum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation